Developing Official Website by using Advertising Language for UMKM Batik Garudeya Kidal - Ririn Pratiwi Suharto; Putri Sekarsari (Universitas Nahdlatul Ulama Blitar, 2026)
This study aimed to develop an official website using advertising language for UMKM Batik Garudeya Kidal. The research used the Design and Development Research (DDR) approach with the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. In the analysis stage, data were collected through observation and interviews, which showed that the UMKM still relied on social media and did not yet have an official website to present complete and structured information about its products. Based on these findings, the researcher developed a website using Wix as the platform. The website was designed to be simple, attractive, and easy to use. Advertising language was applied in the product descriptions to make the content more persuasive and appealing to potential customers. The website contains important information such as business profile, product catalog, pricing, and contact details. The website was then tested through expert validation and user responses. The results showed that the website is in the “very good” category and suitable for use as a promotional media. Field testing results also reached 94.8%, indicating that users found the website easy to use, informative, and visually appealing. Overall, the website is effective in helping UMKM Batik Garudeya Kidal improve its promotion, strengthen its branding, and reach a wider audience through digital media.